Impact of the MoS2 starting material on the dispersion quality and quantity after liquid phase exfoliation - Ott, Steffen; Wolff, Nadja; Rashvand, Farnia; Rao, Vaishnavi J.; Zaumseil, Jana; Backes, Claudia (Chemistry of materials, 2019)
Liquid phase exfoliation has evolved to an important and widely used production technique for 2D materials, giving access to large quantities of nanosheets in the liquid phase. Post-exfoliation size selection, for example by liquid cascade centrifugation, can be applied to tune nanosheet lateral sizes and thicknesses. Various starting materials from powders to high-quality crystals can be used for the process. However, the impact of the starting material on the dispersion quality and quantity is widely unexplored. Here, we performed liquid phase exfoliation combined with liquid cascade centrifugation on six different MoS2 starting materials and assessed nanosheet yield, lateral size, and layer number using established quantitative spectroscopic metrics. We show that both yield and nanosheet dimensions are widely unaffected by the choice of the starting material. In contrast, some impact is observed with respect to optical properties, such as photoluminescence of the monolayers. We find that the photoluminescence intensity is lower for small crystallite bulk materials.
Gesehen am 19.11.2019
Im Titel ist die Zahl "2" tiefer gestellt